An Odd Case of Melena: Chronic Celiac Artery Dissection and Hepatic Arterioduodenal Fistula - Kumar, Lijesh; Philips, Cyriac Abby; Augustine, Philip (Journal of Gastrointestinal and Abdominal Radiology, 2018)
We present the case of a 54-year-old chronic alcoholic man who presented to the emergency department with intermittent melena for 3 days. Imaging revealed a large dissecting pseudoaneurysm of the common hepatic artery with an arterioduodenal fistula in the second part of the duodenum. The pseudoaneurysm and fistula were managed with refined interventional techniques, and supply to the hepatic arteries was salvaged. In cases of melena that are difficult to diagnose through traditional means, early imaging and interventional management can prove beneficial and improve short-term survival.
Keywords: dissecting aneurysm; computed tomography; melena; hepatoduodenal fistula; pseudoaneurysm; common hepatic artery